A yellowing-resistant PVC material and its preparation method and application

By adding organic tin stabilizers, sulfur-containing antioxidants, gas-phase silica and boron nitride to the PVC material, the problem of PVC material being prone to yellowing during radiation sterilization is solved, and its yellowing resistance and tensile strength are significantly improved, meeting the application needs under radiation sterilization conditions.

CN119119653BActive Publication Date: 2025-04-04BAIN MEDICAL EQUIPMENT (GUANGZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411588237.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-04
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

During the radiation sterilization process, PVC materials are prone to degradation, oxidation, intermolecular and intramolecular dehydrochloride reactions, resulting in yellowing of the product, limiting its application in radiation sterilization.

Method used

By adding additives such as organotin stabilizers, sulfur-containing antioxidants, vapor-phase silica and boron nitride, the stability and radiation resistance of PVC materials are improved, the intermolecular and intramolecular dehydrochloride reactions are delayed, and the yellowing phenomenon is reduced.

Benefits of technology

It significantly improves the yellowing resistance of PVC materials, enhances its stable existence under electron beam radiation, improves the tensile strength and comprehensive performance of the materials, and meets the application needs under radiation sterilization conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the field of PVC materials, and specifically discloses a yellowing-resistant PVC material and its preparation method and application. The yellowing-resistant PVC material of the present invention includes the following components in parts by weight: 100 parts of PVC, 1-8 parts of plasticizer, 1-5 parts of organotin stabilizer, 0.5-2 parts of auxiliary stabilizer, 0.05-1 parts of sulfur-containing antioxidant, 0.2-1.5 parts of fatty alcohol polyoxyethylene ether, 0.5-5 parts of inorganic filler, 0.1-2 parts of lubricant, and 0-5 parts of other auxiliary agents; the inorganic filler includes fumed silica and boron nitride. The presence of organotin stabilizer, sulfur-containing antioxidant, fumed silica and boron nitride in the system of the present invention can significantly improve the stability of PVC material under electron beam radiation, improve the yellowing resistance of the material, so as to meet the special requirements that PVC medical devices need to be sterilized under electron beam radiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of PVC materials, and in particular relates to a yellowing-resistant PVC material and a preparation method and application thereof. Background Art

[0002] PVC (polyvinyl chloride) has good mechanical properties, solvent resistance, flame retardancy, and is easy to process and shape. It is widely used in the fields of packaging materials and medical device materials. For safety reasons, electron beam irradiation is widely used to sterilize various medical devices and other materials to achieve efficient, safe, and chemical-free sterilization. For PVC materials, PVC is prone to degradation, oxidation, intermolecular and intramolecular dehydrochlorination reactions during radiation. In particular, intermolecular dehydrochlorination can cause cross-linking or long chain branching between PVC molecules; intramolecular dehydrochlorination can cause the formation of conjugated structures or the generation of peroxides in the PVC molecular chain, making the product yellow in color, thereby limiting its application in radiation sterilization. Summary of the invention

[0003] In view of the problem of yellowing of PVC materials due to radiation in the above-mentioned prior art, the present invention can add various additives to improve the radiation yellowing resistance of PVC materials and broaden their application range.

[0004] In order to achieve the above-mentioned purpose, the present invention provides a yellowing-resistant PVC material, comprising the following components in parts by weight: 100 parts of PVC, 1-8 parts of plasticizer, 1-5 parts of organic tin stabilizer, 0.5-2 parts of auxiliary stabilizer, 0.05-1 parts of sulfur-containing antioxidant, 0.2-1.5 parts of fatty alcohol polyoxyethylene ether, 0.5-5 parts of inorganic filler, 0.1-2 parts of lubricant, and 0-5 parts of other additives; the inorganic filler comprises fumed silica and boron nitride.

[0005] The fumed silica and boron nitride in the system of the present invention have large surface areas and high polarity, and are easy to adsorb active components such as HCl and free radicals generated in the system during the irradiation process, thereby inhibiting the decomposition of PVC to a certain extent. In addition, the fumed silica is weakly alkaline and is more likely to adsorb acidic HCl. Boron nitride has a layered structure and is interspersed in the PVC matrix in combination with the fumed silica, which may extend the diffusion path of molecules, free radicals and other substances therein to a certain extent, reduce the probability of decomposition products or intermediates participating in the reaction, and comprehensively achieve the purpose of significantly improving the yellowing resistance of the PVC material.

[0006] On the one hand, the organotin stabilizer can absorb the HCl released by the thermal degradation of PVC, and on the other hand, it can eliminate unstable substances such as chlorine atoms in the system, thereby playing a passivation effect, thereby improving the stability of PVC; in addition, the stabilizer and auxiliary stabilizer can coordinate with each other to significantly improve the stability of the system and increase the degree to which the material resists the influence of electronic radiation.

[0007] The sulfur-containing antioxidant can capture free radicals in the system of the present invention, and try to avoid certain active substances in the system from reacting with oxygen in the air, thereby improving the yellowing resistance of the material.

[0008] In the system of the present invention, there is no particular limitation on the specific type of PVC, and pure PVC, graft-modified PVC, etc. can be used. For example, PVC graft-modified by methyl methacrylate (MMA) can be used, and the grafting rate can be 1-10wt.%. At the same time, the PVC can be selected to have a polymerization degree greater than 100, and more specifically, a polymerization degree of 500-100.

[0009] Preferably, the plasticizer comprises phthalate, and more preferably at least one of dioctyl phthalate, diisononyl phthalate, diisodecyl phthalate, diisononyl phthalate and diisodecyl phthalate.

[0010] When the content of plasticizer is less than 10%, PVC still maintains the advantages of rigid PVC. Adding a certain amount of plasticizer in the system of the present invention can improve the toughness of the material. While maintaining the characteristics of rigid PVC, the toughness, tensile strength and weather resistance of the PVC material can be significantly improved, thereby improving the comprehensive performance of the material.

[0011] Preferably, the mass ratio of the fumed silicon dioxide and boron nitride is (1-4):1, specifically 1:1, 2:1, 2:1, 3:1, 4:1, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0012] The inventors of the present invention have found that when the content of fumed silica in the system is higher than that of boron nitride, especially when the mass ratio of the two is (1-4):1, the material has better yellowing resistance.

[0013] Preferably, the specific surface area of ​​the fumed silica is 50-500m 2 / g.

[0014] Fumed silica is light in weight, small in particle size, large in specific surface area, and slightly alkaline, which is conducive to the adsorption of substances such as HCl. Especially at the above-mentioned specific surface area, it is more conducive to improving the defect of yellowing of the material under electron beam radiation.

[0015] Preferably, the average particle size of the boron nitride is 100-1000 nm.

[0016] Boron nitride is hexagonal boron nitride with a layered structure. It has a certain lubricity and good compatibility with PVC. The average particle size of boron nitride has a certain influence on the dispersion effect in the system and the subsequent adsorption effect under electron beam radiation. It is easier to adsorb and disperse when selecting nano-sized particles, but the particle size should not be too small. If the particle size is too small, the surface energy is large, and it is easy to agglomerate, resulting in poor dispersion effect, which affects the degree to which it improves the yellowing resistance of the material.

[0017] In addition, as inorganic fillers, fumed silica and boron nitride have relatively stable performance and can stably exist under electron beam irradiation, thereby enhancing the tensile strength of PVC materials and improving the tensile strength after electron beam irradiation.

[0018] Preferably, the organic tin stabilizer includes at least one of di-n-octyltin dilaurate, tin methyl mercaptan, dibutyltin bis(butyl maleate), and di(β-butoxycarbonylethyl)tin di(isooctylthioacetate).

[0019] Preferably, the sulfur-containing antioxidant includes at least one of distearyl thiodipropionate, dilauryl thiodipropionate, and ditridecyl 3,3-thiodipropionate.

[0020] Preferably, the mass ratio of the organotin stabilizer to the sulfur-containing antioxidant is (1.5-3):(0.1-1.2), and more preferably, (1.7-2.5):(0.2-1).

[0021] The system of the present invention contains both an organic tin stabilizer and a sulfur-containing antioxidant, which synergistically improve the stability of the material and the yellowing resistance of the material.

[0022] Preferably, the auxiliary stabilizer includes at least one of epoxidized soybean oil and epoxidized linseed oil.

[0023] Auxiliary stabilizers, with epoxy groups, can further cooperate with organic tin stabilizers to improve the stability of materials under electron beam radiation and improve the material's yellowing resistance.

[0024] Preferably, the fatty alcohol polyoxyethylene ether includes at least one of polyoxyethylene stearyl ether and polyoxyethylene lauryl ether.

[0025] Preferably, the HLB of the fatty alcohol polyoxyethylene ether is 9-19, specifically 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0026] Fatty alcohol polyoxyethylene ether surfactants can perform certain wetting modification on inorganic fillers, thereby improving the compatibility between the filler and the matrix and enhancing the filler's role in improving the yellowing resistance. Different HLBs may have different degrees of affinity for the material, so different HLBs have a certain influence on the material's yellowing resistance. The inventors of the present invention have found that the material has better yellowing resistance at the above-mentioned HLB.

[0027] Preferably, the lubricant includes at least one of polyethylene wax, oxidized polyethylene wax, stearic acid, butyl stearate, stearic acid monoglyceride, stearic acid alcohol, stearyl stearate, oleic acid monoglyceride, and ricinoleic acid monoglyceride.

[0028] Preferably, the other additives include the following components by weight: 0.1-5 parts of alcohols, 0.1-2 parts of colorants, and 0.1-5 parts of flame retardants. The present invention can also add some other additives, such as colorants, flame retardants, etc., to improve the comprehensive performance of the material.

[0029] Preferably, the alcohols include at least one of polyethylene glycol, polypropylene glycol, polybutylene glycol, pentaerythritol, dipentaerythritol, tripentaerythritol, trimethylolethane, di(trimethylol)propane, polyvinyl alcohol, di(trimethylol)ethane, trihydroxytetramethylolpropane and sorbitol.

[0030] Preferably, the molecular weight of the alcohol is 200-4000, and more preferably, the molecular weight of the alcohol is 1000-2500.

[0031] In the system of the present invention, alcohols can remove or reduce substances such as free radicals in the system, further improving the yellowing resistance of the material.

[0032] The present invention also provides a method for preparing the yellowing-resistant PVC material, comprising the following steps: uniformly mixing, melt-kneading and extruding the raw materials in sequence to obtain the yellowing-resistant PVC material.

[0033] Preferably, the temperature of the melt kneading is 160-200°C.

[0034] The present invention also provides an application of the yellowing-resistant PVC material in the preparation of medical devices, which can specifically include the preparation of artificial dialyzers, blood oxygenators, blood separators, anesthesia evaporators and other equipment.

[0035] Compared with the prior art, the present invention has the following beneficial effects: the system of the present invention contains an organic tin stabilizer, a sulfur-containing antioxidant, fumed silica and boron nitride, which can significantly improve the stability of the PVC material under electron beam radiation and improve the yellowing resistance of the material to meet the special requirements of PVC medical devices that need to be sterilized under electron beam radiation. DETAILED DESCRIPTION

[0036] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0037] PVC: A mixture of PVC powder (S-60, Formosa Plastics Ningbo, DP 780 ± 30) and methyl methacrylate (MMA) was added into an extruder and melt-extruded at 150 °C, wherein the screw speed was 40 rpm, and MMA accounted for 7% of the total mass of PVC and MMA.

[0038] Plasticizer: dioctyl phthalate (DOP), Shandong Beisu Chemical Industry.

[0039] Stabilizer 1: Dioctyltin dilaurate, Guangzhou Yuanda New Materials Co., Ltd.

[0040] Stabilizer 2: Methyltin mercaptan, Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0041] Stabilizer 3: zinc stearate, commercially available.

[0042] Auxiliary stabilizer: Epoxidized soybean oil, KD-106, Dongguan Boxuan Industrial Investment Co., Ltd.

[0043] Antioxidant 1: distearyl thiodipropionate, Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0044] Antioxidant 2: dilauryl thiodipropionate, commercially available.

[0045] Antioxidant 3: pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate (1010), commercially available.

[0046] Surfactant 1: polyoxyethylene lauryl ether, HLB 9, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0047] Surfactant 2: polyoxyethylene (10) octadecyl ether, HLB 12, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0048] Surfactant 3: polyoxyethylene (100) stearyl ether, HLB 18.8, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0049] Surfactant 4: sodium lauryl polyoxyethylene ether sulfate, HLB 9-16.5, commercially available.

[0050] Fumed silica: PA976463, surface area 200m2 / g, Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0051] Hexagonal boron nitride: average particle size is 500nm, McLean.

[0052] Lubricant: Polyethylene wax, commercially available.

[0053] Alcohol: polypropylene glycol PPG-2000, commercially available.

[0054] Example 1

[0055] A method for preparing a yellowing-resistant PVC material in this embodiment includes the following steps:

[0056] (1) Mix the components evenly according to the raw material ratio in Table 1-2;

[0057] (2) The mixture is mixed and kneaded in an open mixer to produce sheets (temperature 110-180°C), and then pressed into 2 mm thick long sheets through a plate pressing machine (170°C).

[0058] Example 2-3

[0059] Compared with Example 1, Example 2-3 differs in that the mass ratio of fumed silicon dioxide to boron nitride is different, and the rest are the same.

[0060] Embodiment 4-5

[0061] Compared with Example 1, Example 4-5 differs in that the total weight portions of fumed silicon dioxide and boron nitride are different, and the rest are the same.

[0062] Example 6

[0063] Compared with Example 1, this embodiment differs in that the type of stabilizer is different, and the rest is the same.

[0064] Example 7

[0065] Compared with Example 1, this embodiment differs in that the type of antioxidant is different, and the rest is the same.

[0066] Embodiment 8-9

[0067] Compared with Example 1, the difference between Example 8-9 is that the types of surfactants are different, and the rest are the same.

[0068] Example 10

[0069] The difference between this embodiment and embodiment 1 is that PPG is not added in this embodiment, and the rest is the same.

[0070] Examples 11-12

[0071] The difference between this embodiment and embodiment 1 is that the weight portions of the stabilizer and the antioxidant in this embodiment are different.

[0072] Comparative Examples 1-4

[0073] Compared with Example 1, Comparative Examples 1-4 differ in that the weight portions of fumed silicon dioxide and boron nitride added are different, and the rest are the same.

[0074] Comparative Example 5

[0075] Compared with Example 1, this comparative example differs in the type of stabilizer and the rest is the same.

[0076] Comparative Example 6

[0077] The difference between this comparative example and Example 1 is that the type of antioxidant is different, and the rest is the same.

[0078] Comparative Example 7

[0079] The difference between this comparative example and Example 1 is that the type of surfactant is different, and the rest is the same.

[0080] Comparative Example 8

[0081] The difference between this comparative example and Example 1 is that no antioxidant is added, and the rest is the same.

[0082] Comparative Example 9

[0083] The difference between this comparative example and Example 1 is that no stabilizer is added, and the rest is the same.

[0084] Table 1

[0085]

[0086] Table 2

[0087]

[0088] Performance Testing:

[0089] (1) The sheets in the above-mentioned embodiments and comparative examples were subjected to electron beam irradiation with an irradiation dose of 25 kGy, and the yellowing index of the sheets before and after irradiation was tested, and then the yellowing index change rate was calculated. The specific formula for the yellowing index change rate is: RYI (%) = (Y1-Y0) / Y0*100, where RYI yellowing index change rate, Y0 is the yellowing index of the unirradiated sample, Y1 is the yellowing index of the irradiated sample, and RYI ≤ 15% is considered qualified. The yellowing index change rates in the embodiments of the present invention and the comparative examples are shown in Table 3.

[0090] (2) According to the standard of GB / T1040-2006-2, the tensile strength and its change rate of the sheet before and after electron beam irradiation were tested. The calculation formula of the tensile strength change rate is: X (%) = (R1-Y0) / R0*100, where X is the change rate of tensile strength, R0 is the tensile strength of the unirradiated sample, and R1 is the tensile strength of the irradiated sample. X≤20% is considered qualified, and X≤10% is considered good. The test shows that the tensile strength in Examples 1-12 of the present invention is 35-45 MPa, and the specific tensile strength change rate is shown in Table 3.

[0091] Table 3

[0092]

[0093] It can be seen from the above embodiments that in the system of the present invention, the PVC material of the present invention can maintain good anti-yellowing and anti-tensile properties under electron beam radiation, can meet the special requirements of actual medical devices for sterilization and other treatments under electron beam radiation, and can further expand the application scenarios of this type of PVC material.

[0094] It can be seen from Example 1 and Comparative Examples 1-3 that the fumed silica and boron nitride in the system of the present invention have large surface areas and high polarity, and are easy to adsorb active components such as HCl molecules and free radicals generated in the system during the irradiation process, thereby inhibiting the decomposition of PVC to a certain extent; boron nitride has a layered structure, and cooperates with fumed silica to be interspersed in the PVC matrix, which may extend the diffusion path of gases, free radicals and other substances therein to a certain extent, thereby comprehensively achieving the purpose of significantly improving the yellowing resistance of PVC materials. In addition, fumed silica and boron nitride, as inorganic fillers, have relatively stable performance and can stably exist under electron beam radiation, thereby enhancing the tensile strength of PVC materials and improving the tensile strength after electron beam radiation.

[0095] It can be seen from Examples 1-5 and Comparative Example 4 that the mass ratio of fumed silica and boron nitride and the total content in the system have a certain influence on the yellowing resistance and tensile strength of the system. The inventors of the present invention found that when the content of fumed silica in the system is higher than that of boron nitride, especially when the mass ratio of the two is (1-4):1, the yellowing resistance of the material is better. When the total mass of fumed silica and boron nitride is too much, the compatibility of the two in the system is limited, resulting in poor uniformity within the system, which will significantly reduce its tensile strength.

[0096] It can be seen from Examples 1 and 6 and Comparative Examples 5 and 8 that the stabilizer can absorb HCl released by thermal degradation of PVC on the one hand, and eliminate unstable chlorine atoms and other substances in the system on the other hand, thereby achieving a passivation effect, thereby improving the stability of PVC; in addition, the stabilizer and the auxiliary stabilizer can be coordinated and cooperated to significantly improve the stability of the system and the degree to which the material resists the influence of radiation. At the same time, compared with other types of stabilizers, the organic tin stabilizer in the system of the present invention has a better effect on improving the yellowing resistance of the material.

[0097] The antioxidant can capture free radicals in the system of the present invention, and try to avoid certain active substances in the system from reacting with oxygen in the air, thereby improving the yellowing resistance of the material. It can be seen from Examples 1, 7 and Comparative Example 6 that compared with other stabilizers, the use of sulfur-containing antioxidants in the system of the present invention has a better yellowing resistance effect on the material.

[0098] From Examples 1, 8-9 and Comparative Example 7, there are inorganic fillers in the system of the present invention, and the fatty alcohol polyoxyethylene ether surfactant can modify the filler to a certain extent, thereby improving the compatibility of the filler with the matrix and enhancing the degree to which the filler improves the yellowing resistance. Compared with other types of anionic surfactants, the fatty alcohol polyoxyethylene ether surfactant may have a greater affinity with water molecules, resulting in a relatively poorer affinity with the system, resulting in limited effect on improving the yellowing resistance of the system.

[0099] It can be seen from Examples 1 and 10 that the presence of polyhydroxyl groups in alcohols can further capture substances such as free radicals in the system, eliminate free radicals, and improve the yellowing resistance of the material.

[0100] It can be seen from the above embodiments and comparative examples that in the system of the present invention, PVC is used as the matrix, and an organic tin stabilizer, a sulfur-containing antioxidant, fumed silica, and boron nitride are added, which can significantly improve the yellowing resistance of the material. In addition, in combination with other auxiliary stabilizers, lubricants, alcohols, and plasticizers, good mechanical properties can be obtained on the basis of achieving relatively good yellowing resistance, avoiding the obvious brittle defect after electron radiation, and achieving good comprehensive performance.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A yellowing-resistant PVC material, characterized in that: The composition comprises the following components in parts by weight: 100 parts of PVC, 1-8 parts of plasticizer, 1-5 parts of organic tin stabilizer, 0.5-2 parts of auxiliary stabilizer, 0.05-1 parts of sulfur-containing antioxidant, 0.2-1.5 parts of fatty alcohol polyoxyethylene ether, 0.5-5 parts of inorganic filler, 0.1-2 parts of lubricant, and 0-5 parts of other additives; the inorganic filler includes fumed silica and boron nitride; the mass ratio of the fumed silica to boron nitride is (1-4):1; the other additives include the following components in parts by weight: 0.1-5 parts of alcohols; the alcohols include at least one of polyethylene glycol, polypropylene glycol, polybutylene glycol, pentaerythritol, dipentaerythritol, tripentaerythritol, trimethylolethane, di(trimethylol)propane, polyvinyl alcohol, di(trimethylol)ethane, trihydroxytetramethylolpropane, and sorbitol; the specific surface area of ​​the fumed silica is 50-500m 2 / g; the HLB of the fatty alcohol polyoxyethylene ether is 9-19.

2. The yellowing-resistant PVC material according to claim 1, characterized in that: The organic tin stabilizer includes at least one of dioctyltin dilaurate, tin methyl mercaptan, dibutyltin bismaleate, and di(β-butoxyformylethyl)tin di(isooctylthioacetate).

3. The yellowing-resistant PVC material according to claim 1, characterized in that: The sulfur-containing antioxidant includes at least one of distearyl thiodipropionate, dilauryl thiodipropionate, and ditridecyl 3,3-thiodipropionate.

4. The yellowing-resistant PVC material according to claim 1, characterized in that: The fatty alcohol polyoxyethylene ether includes at least one of polyoxyethylene octadecyl ether and polyoxyethylene lauryl ether.

5. The yellowing-resistant PVC material according to claim 1, characterized in that: Include at least one of the following: The mass ratio of the organotin stabilizer to the sulfur-containing antioxidant is (1.5-3): (0.1-1.2); The lubricant comprises at least one of polyethylene wax, oxidized polyethylene wax, stearic acid, butyl stearate, stearic acid monoglyceride, stearic acid alcohol, stearyl stearate, oleic acid monoglyceride, and ricinoleic acid monoglyceride; The plasticizers include phthalates.

6. The yellowing-resistant PVC material according to claim 1, characterized in that: The other auxiliary agents also include the following components in parts by weight: 0.1-2 parts of colorant and 0.1-5 parts of flame retardant.

7. A method for preparing the yellowing-resistant PVC material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing, melting and kneading, and extruding the raw materials in sequence to obtain the yellowing-resistant PVC material.

8. Use of the yellowing-resistant PVC material according to any one of claims 1 to 6 in the preparation of medical devices.

Citation Information

Patent Citations

  • Method for regulating trap distribution of polyethylene material for nuclear power plant cable based on micro-nano particles

    CN110041597A

  • High-gloss spraying-free plastic particles and preparation process thereof

    CN114058149A

  • Radiation-resistant hard PVC (polyvinyl chloride) material as well as preparation method and application thereof

    CN114685925A